Conditioned Medium From Azurin-Expressing Human Mesenchymal Stromal Cells Demonstrates Antitumor Activity Against Breast and Lung Cancer Cell Lines - Silva, Marília; Monteiro, Gabriel Amaro; Fialho, Arsenio M.; Bernardes, Nuno; da Silva, Cláudia Lobato (Frontiers in Cell and Developmental Biology, 2020)
Recently, cell-based therapies have been explored as a strategy to enhance the specificity of anti-cancer therapeutic agents. In this perspective, human mesenchymal stromal cells (MSC) hold a promising future as cell delivery systems for anti-cancer proteins due to their unique biological features. In this study, we engineered human MSC to secrete a human codon-optimized version of azurin (hazu), a bacterial protein that has demonstrated anti-cancer activity towards different cancer models both in vitro and in vivo. To this end, microporation was used to deliver plasmid DNA encoding azurin into MSC derived from bone marrow (BM) and umbilical cord matrix (UCM), leading to expression and secretion of hazu to the conditioned medium (CM). Engineered hazu-MSC were shown to preserve tumor tropism towards breast (MCF-7) and lung (A549) cancer cell lines, comparable to non modified MSC. Azurin was detected in the CM of transfected MSC and, upon treatment with hazu-MSC-CM, we observed a decrease in cancer cell proliferation, migration and invasion; and an increase in cell death for both cancer cell lines. Moreover, expression of azurin caused no changes in MSC expression profile of cytokines relevant in the context of cancer progression, thus suggesting that the antitumoral effects induced by hazu-MSC secretome might be due to the presence of azurin independently. In conclusion, data shown herein indicate that MSC produced-azurin in a CM configuration, elicit an anti-cancer effect.